Lingkungan Ramah Anak pada Sekolah Taman Kanak-Kanak - Diyanti, Ayu Oktira; Amiuza, Chairil Budiarto; Mustikawati, Triandriani (RUAS (Review of Urbanism and Architectural Studies), 2014)
Physical environment (in this case is kindergarten) needs to be considered because it has a frequent contact either physically or mentally with children. Based on this issue, kindergarten should provides facilities that appropriate to children’s growth and development process, and also to their characteristic. The purpose of this research was identifying child-friendly environment criterias. The method used was literature comparation about child-friendly criterias in kindergarten. The result showed that child-friendly criterias in kindergarten were three factors: safety, comfort, and stimulation either in exterior element or interior element of kindergarten environment.Keywords: children, kindergarten, exterior, interior